Inducible clindamycin resistance in Staphylococcus aureus isolates recovered from Mashhad, Iran - Seifi, N (Tehran University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVES: Staphylococcus aureus is an important agent in hospital and community-associated infections, causing high morbidity and mortality. Introduction of the new antimicrobial classes for this pathogen has been usually followed by the emergence of resistant strains through multiple mechanisms. For instance, resistance to clindamycin (CLI)can be constitutive or inducible. Inducible clindamycin resistance which may lead to treatment failure can simply be identified by performing D-test. The aim of this study was to determine the prevalence of inducible clindamycin resistance among Staphylococcus aureus isolates by D-test method. MATERIALS AND METHODS: This was a cross-sectional study conducted on 211 non-duplicated S. aureus isolates in Imam Reza hospital of Mashhad during 2010. Susceptibility to oxacillin, cefoxitin, erythromycin and clindamycin was performed by agar disk diffusion method according to CLSI guidelines and D-shaped clindamycin susceptibility patterns where considered as D-test positive (D(+)). RESULTS: Of 211 S. aureus isolates,88 (41.7%) were methicillin resistant. It was found that of 88 MRSA isolates, 78 (88.6%) were erythromycin (ERY) resistant and 46 (52.3%) were CLI resistant. ERY and CLI resistance in MSSA strains was 22% and 10.6% respectively. Inducible clindamycin resistance was detected in 18 (20.5%) MRSA isolates. 47(53.4%) of MRSA isolates and 9 (7.3%) of MSSA showed constitutive MLS(B) phenotype. CONCLUSION: In conclusion, we found a high prevalence of inducible clindamycin resistance phenotype in our region. We recommend that whenever clindamycin is intended to be used for S. aureus infections, D-test should be performed to facilitate the appropriate treatment of patients.